PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KETAHANMALANGAN KEPALA SEKOLAH TERHADAP KINERJA GURU DI SEKOLAH DASAR NEGERI KECAMATAN KARANG AGUNG ILIR - Abdul Aksa; Dessy Wardiah; Andi Rahman (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
The disparity in teaching work ethic and the gap in educator performance in tidal waters areas due to limited physical logistics are the background to this research activity. These operational problems trigger the vulnerability of work burnout levels, instructional passivity, and a continuous decline in the quality of managerial effectiveness of educational units. The main focus of this scientific study is to analyze the magnitude of the influence of transformational leadership and principal resilience partially or simultaneously on the quality of teacher performance. The steps of the quantitative approach with the survey method are operated using a structured questionnaire instrument with a five-degree Likert scale model. Sampling is carried out via a total sampling technique involving the entire active population of 99 respondents at the Karang Agung Ilir District Public Elementary School. The numerical data processing procedure is executed through multiple linear regression analysis modeling using SPSS software. Quantitative data empirically reveals a positive functional contribution in the same direction through the formation of the estimation formula Y = 18.799 + 0.432X1 + 0.377X2. Partially, the transformational style variable obtained a t-value of 5.722, while resilience achieved a t-value of 5.333. The simultaneous accumulation of combined contributions resulted in an F-value of 27.073 with a total effective determination of 36.1 percent. The main conclusion confirms that the hybridization of inspirational role models and psychological resilience of leaders has proven to be very reliable in maintaining the stability of teacher teaching productivity. ABSTRAK Disparitas etos kerja pengajaran serta adanya kesenjangan performa pendidik di daerah perairan pasang surut akibat keterbatasan logistik fisik melatarbelakangi kegiatan penelitian ini. Masalah operasional tersebut memicu kerentanan tingkat kejenuhan kerja, pasivitas instruksional, serta penurunan mutu efektivitas manajerial satuan pendidikan secara berkelanjutan. Fokus utama kajian ilmiah ini adalah menganalisis besaran pengaruh kepemimpinan transformasional dan ketahanmalangan kepala sekolah secara parsial maupun simultan terhadap mutu kinerja guru. Langkah-langkah pendekatan kuantitatif dengan metode survei ini dioperasikan menggunakan instrumen kuesioner angket terstruktur model skala Likert lima derajat. Penarikan sampel dijalankan via teknik total sampling yang melibatkan seluruh populasi aktif sejumlah 99 responden di Sekolah Dasar Negeri Kecamatan Karang Agung Ilir. Prosedur pengolahan data numerik dieksekusi melalui permodelan analisis regresi linier berganda memakai bantuan perangkat lunak SPSS. Data kuantitatif secara empiris menyingkap kontribusi positif fungsional yang searah melalui bentukan rumus estimasi Y = 18,799 + 0,432X1 + 0,377X2. Secara parsial, variabel gaya transformasional memperoleh nilai t-hitung sebesar 5,722, sedangkan ketahanmalangan meraih skor t-hitung sejumlah 5,333. Akumulasi kontribusi gabungan secara simultan menorehkan parameter F-hitung sebesar 27,073 dengan total determinasi efektif sebesar 36,1 persen. Simpulan utama menegaskan bahwa hibridasi keteladanan inspiratif serta ketangguhan psikologis pemimpin terbukti sangat andal memelihara stabilitas produktivitas mengajar guru.